Organic petrographic, geochemical, and sequence stratigraphic analyses for evaluating the hydrocarbon potential of Middle Jurassic–Lower Cretaceous rocks in Shushan Basin, northwestern Egypt - Aljahdali, Mohammed H.; Deaf, Amr S.; Gentzis, Thomas; Bantan, Rashad A.; Abu-Zied, Ramadan H.; Carvajal-Ortiz, Humberto; Khalaf, Miran M. (Frontiers in Earth Science, 2023)
Integrated organic petrographic and geochemical analyses were made on organic-rich marine carbonate and mixed clastic-carbonate rocks of Middle–Late Jurassic and Early Cretaceous age from the Shushan Basin, Egypt to evaluate their hydrocarbon potential. Analyses allowed the identification of depositional settings, paleoclimate, and three third order genetic stratigraphic sequences (SQ) with deposits assigned to highstand (HST), lowstand (LST) and transgressive systems tracts (TST). Deposition of the source rocks in the rifting Shushan Basin resulted from the interaction between Neotethyan sea level changes, tectonic, and climate. The good reducing conditions developed during the Neotethyan Middle–Late Jurassic (Bajocian–Kimmeridgian) second order sea level rises and the climatically induced carbonate sedimentation resulted in the deposition of the organic-rich carbonates of the Khatatba Formation (SQ 1, early–middle TST) in inner–middle shelf settings under anoxic–dysoxic conditions. The Late Jurassic (late Kimmeridgian) uplifting resulted in the deposition of the organic-lean mixed clastic–carbonate strata of the Masajid Formation (SQ 1, latest TST) in the same shelfal and reducing conditions, which experienced a notable dilution of organic matter. The late TST deposits of SQ 1 are good to very good oil-producing source rocks, where they show average good to very good generative potential of late mature (late oil-to early wet gas-window) highly oil-prone organic matter. The Early Cretaceous (Valanginian–Albian) uplifting associated with the rifting of the Shushan Basin overprinted the Neotethyan late Valanginian–Hauterivian second order sea level rises, Aptian second order highstand sea level, and Albian second order sea level rise. The coeval climatic shift toward more humid conditions resulted in the clastic-dominated deposition of the organic-lean regressive units of SQ 2 (HST and LST of Alam El Bueib, Alamein, and Dahab formations) and SQ 3 (HST and LST of the lower–upper Kharita Formation) in marginal marine settings under anoxic–dysoxic to oxic conditions. The HST and LST deposits of the SQ 2 and SQ 3 show poor to good organic richness of early–mid mature (early–peak oil-window) oil/gas-prone and gas/oil-prone organic matter, respectively and exhibit average fair oil source rock potential with no gas generation.